2013
DOI: 10.4161/cc.23963
|View full text |Cite
|
Sign up to set email alerts
|

The RUNX1 transcription factor is expressed in serous epithelial ovarian carcinoma and contributes to cell proliferation, migration and invasion

Abstract: Previously, we have identified the RUNX1 gene as hypomethylated and overexpressed in post-chemotherapy (CT) primary cultures derived from epithelial ovarian cancer (EOC) patients, when compared with primary cultures derived from matched primary (prior to CT) tumors. Here we show that RUNX1 displays a trend of hypomethylation, although not significant, in omental metastases compared with primary EOC tumors. Surprisingly, RUNX1 displayed significantly higher expression not only in metastatic tissue, but also in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 86 publications
7
109
0
Order By: Relevance
“…These findings are consistent with the emerging role of RUNX1 in controlling cell motility and migration in other biological systems. Our laboratory has previously shown that Runx1 depletion in breast cancer cells results in a decreased migration and invasion phenotype (Browne et al., 2015); similar results were found in ovarian cancer cells (Keita et al., 2013). Likewise, Runx1b is responsible for inducing a cell adhesion and migration program prior to release of mouse hematopoietic stem cells from hemogenic endothelium (Lie-A-Ling et al., 2014).…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with the emerging role of RUNX1 in controlling cell motility and migration in other biological systems. Our laboratory has previously shown that Runx1 depletion in breast cancer cells results in a decreased migration and invasion phenotype (Browne et al., 2015); similar results were found in ovarian cancer cells (Keita et al., 2013). Likewise, Runx1b is responsible for inducing a cell adhesion and migration program prior to release of mouse hematopoietic stem cells from hemogenic endothelium (Lie-A-Ling et al., 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Our study describes, for the first time, a clinically relevant mechanism for control of Runx1 in breast cancer through miRNA regulation. These studies showing that miR-378 expression inhibits breast cancer cell activities are relevant to other cancers where Runx1 is associated with tumorigenesis [68]; also, loss of miR-378 is associated with cancers [4244], thereby becoming a viable therapeutic strategy. MicroRNAs are emerging as therapeutic molecules [23, 75] and a replacement therapy using a miR-34 mimic (called MRX34), a master tumor suppressor, was first administered to cancer patients in a multicenter, open-label phase I clinical trial, due to be completed later this year.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in expression corresponded to the degree of differentiation in PTC, FTC, and ATC with the greatest differences observed between normal and ATC cells. Since Runx1, another member of the Runx family, has also been implicated in breast (48), ovarian (49), prostate (50) and solid tumors, we also determined its relative expression. Runx 1 protein levels were not correlated with thyroid cancer cell types ( Figure 1A).…”
Section: Runx2 and Tr␤ Are Reciprocally Expressed In Thyroid Benign Amentioning
confidence: 99%